Effects of More-Affected vs. Less-Affected Motor Cortex tDCS in Parkinson’s Disease - Cosentino, Giuseppe; Valentino, Francesca; Todisco, Massimiliano; Alfonsi, Enrico; Davì, Rosaria; Savettieri, Giovanni; Fierro, Brigida; D’Amelio, Marco; Brighina, Filippo (Frontiers in Human Neuroscience, 2017)
Objective. To evaluate therapeutic potential of different montages of transcranial direct current stimulation (tDCS) in Parkinson’s Disease (PD) patients with asymmetric motor symptoms. Materials and Methods. Fourteen patients with asymmetric PD underwent, while on treatment, seven separate sessions including electrophysiological and clinical evaluation at baseline and after anodal, cathodal and sham tDCS of the primary motor cortex (M1) of the two hemispheres. Changes in motor cortical excitability were evaluated by transcranial magnetic stimulation. Effects on motor symptoms were assessed by testing finger tapping and upper limb bradykinesia, and by using the Italian validated Movement Disorder Society revision of the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS). Results. Only anodal tDCS of the more-affected M1 (contralateral to the more-affected body side) and cathodal tDCS of the less-affected M1 (contralateral to the less-affected body side) were able to induce significant changes in cortical excitability, i.e. facilitation and inhibition of the motor evoked potentials respectively. The motor performances of both hands significantly improved after anodal tDCS of the more-affected M1, as well as after cathodal tDCS of the less-affected one. Conclusions. Our findings support the potential usefulness of tDCS as add-on treatment for asymmetric PD, also providing interesting clues on the possible pathophysiological role played by an asymmetric activation of homologous motor cortical areas in PD.